Adverse events induced by nivolumab and ipilimumab combination regimens. (November 2021) - Somekawa, Kohei; Horita, Nobuyuki; Kaneko, Ayami; Tagami, Yoichi; Fukuda, Nobuhiko; Matsumoto, Hiromi; Namkoong, Ho; Fujiwara, Yu; Minegishi, Kaoru; Fukumoto, Takeshi; Watanabe, Keisuke; Hara, Yu; et al.
Background: No meta-analysis has assessed the pooled frequencies of adverse events (AEs) induced by concomitant nivolumab plus ipilimumab regimen for anticancer-medications-naïve malignancies. Furthermore, no meta-analysis has compared detailed safety profiles between four doses of nivolumab 3 mg/kg plus ipilimumab 1 mg/kg every 3 weeks (N3I1) and four doses of nivolumab 1 mg/kg plus ipilimumab 3 mg/kg every 3 weeks (N1I3). Objectives of this study was estimating AE frequencies, and comparison of AE frequencies between N3I1 and N1I3 regimens. Methods: Four major electronic databases were searched; both interventional and observational studies were included. All primary cancer types were permitted. Patients should not have been previously treated with any anti-cancer medications. The frequency of AEs was pooled using a random-model meta-analysis using the generic inverse variance method. Protocol registration: UMIN000044090. Results: Forty articles representing 48 populations with 4, 677 patients were included in the study. The pooled frequencies for key indicators were as follows: any AE, 81.3% (95% confidence interval (CI) 77.5-85.1); grade 3 or higher AE, 40.6% (95% CI: 35.7–45.5); serious AE, 32.7% (95% CI: 22.4–43.1); AE leading to discontinuation, 28.3% (95% CI: 23.7–32.8); and treatment-related death, 0.7% (95% CI: 0.4–1.1). AEs with the highest incidence were fatigue (27.9%, 95% CI: 22.6–33.3), followed by diarrhea (26.0%, 95% CI: 21.5–30.5), pruritus (24.6%, 95% CI: 20.3–28.8), rash (24.0% 95% CI: 19.3–28.7), and elevated aspartate aminotransferase (21.2%, 95% CI: 14.9–27.5). Subgroup analyses demonstrated that N3I1, compared to N1I3, less frequently induced any AE (N1I3 95.7%, N3I1 84.5%, p  = 0.003), grade 3 or higher AE (N1I3 64.3%, N3I1 35.7%, p  < 0.001), and serious AE (N1I3 61.4%, N3I1 47.8%, p  = 0.004). Conclusions: Approximately 40% of patients had grade 3 or higher AE. The N3I1 regimen was substantiated to trigger fewer any AEs, high grade AEs, and serious AE than the N1I3 regimen.